Limb vascular function in women—Effects of female sex hormones and physical activity. Issue 1 (6th February 2018) - Hellsten, Y.; Gliemann, L.
Abstract : Throughout life, women are subjected to both acute fluctuations in sex hormones, associated with the menstrual cycle, and chronic changes following the onset of menopause. Female sex hormones, and in particular estrogen, strongly influence cardiovascular function such as the regulation of vascular tone and oxidative stress and thereby functions such as oxygen delivery and blood pressure. The acute hormonal fluctuations do not substantially impact health, but their influence should be considered with regard to measurements of vascular function. The chronic hormonal change with menopause strongly impacts the vasculature and markedly increases the risk of cardiovascular events. Physical activity activates signaling pathways also triggered by estrogen; therefore, exercise training could be an effective means of reducing the deleterious effects of estrogen loss at menopause. However, findings are divergent with some reporting marked improvements in vascular health with physical activity and others showing lower gains compared to age‐matched males. Potential explanations for this discrepancy in findings are timing after menopause and training mode, aspects that should be further addressed in future studies. Physical activity should be recommended for women of all ages, but the most essential timing for maintenance of vascular health may be from menopause and onwards.